An Evolving Random Network and Its Asymptotic Structure (Communications in Mathematical Research, 2021)
In this paper, we propose an evolving random network. The model is alinear combination of preferential attachment model and uniform model. We showthat scaling limit distribution of the number of leaves at time $n$ is approximatedby normal distribution and the proportional degree sequence obeys power law. Thebranching structure and maximum degree are also discussed in this paper.
Keywords: random network; scale-free graph; degree sequence.